2021
DOI: 10.1186/s13071-021-04927-8
|View full text |Cite
|
Sign up to set email alerts
|

Equine attachment site preferences and seasonality of common North American ticks: Amblyomma americanum, Dermacentor albipictus, and Ixodes scapularis

Abstract: Background Ticks are common on horses, but recent publications characterizing equine tick infestations in North America are lacking. Methods To further understand attachment site preferences of common ticks of horses, and to document the seasonality of equine tick infestation in northeastern Oklahoma, horses from eight farms were evaluated twice a month over a 1-year period. Each horse was systematically inspected beginning at the head and moving c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Product tests in the laboratory on other tick species— Dermacentor albipictus (Packard), Dermacentor reticulatus (Fabricius), Ixodes ricinus (L.), Rhipicephalus sanguineus sensu lato, and Rhipicephalus ( Boophilus ) microplus (Canestrini)—also demonstrated high mortality under high temperature and humidity conditions (>80%RH) ( Table 4 ). Dermacentor albipictus larvae, a one-host tick that parasitizes ungulates like cattle, horses, and moose [ 35 , 36 , 37 ] has received the most attention. Although 100% mortality is achievable in vitro after three weeks when immersed or sprayed, broadcast applications of a granular formulation achieved a reduced level of mortality (89%).…”
Section: Metarhizium -Based Formulationsmentioning
confidence: 99%
“…Product tests in the laboratory on other tick species— Dermacentor albipictus (Packard), Dermacentor reticulatus (Fabricius), Ixodes ricinus (L.), Rhipicephalus sanguineus sensu lato, and Rhipicephalus ( Boophilus ) microplus (Canestrini)—also demonstrated high mortality under high temperature and humidity conditions (>80%RH) ( Table 4 ). Dermacentor albipictus larvae, a one-host tick that parasitizes ungulates like cattle, horses, and moose [ 35 , 36 , 37 ] has received the most attention. Although 100% mortality is achievable in vitro after three weeks when immersed or sprayed, broadcast applications of a granular formulation achieved a reduced level of mortality (89%).…”
Section: Metarhizium -Based Formulationsmentioning
confidence: 99%
“…The attachment site of ticks has been studied in the context of both animal and human tick preference. In Oklahoma, a study of horses indicated that A. americanum preferentially bites the inguinal area, while I. scapularis and D. albipictus , the moose-tick, primarily bite the chest and axillary region, with D. albipictus often being found on the back 18 . A survey of dogs and cats across the US identified a similar distribution of ticks on dogs, with the attachment being most common on the abdomen, axillary and inguinal regions.…”
Section: Discussionmentioning
confidence: 99%
“…The attachment site of ticks has been studied in the context of both animal and human tick preference. In Oklahoma, a study of horses indicated that A. americanum preferentially bites the inguinal area while I. scapularis and D. albipictus, the moose-tick, primarily bite the chest and axillary region with D. albipictus additionally often being found on the back [31]. A survey of dogs and cats across the US identi ed a similar distribution of ticks on dogs, with the attachment being most common on the abdomen, axillary and inguinal regions.…”
Section: Discussionmentioning
confidence: 99%